DESKRIPSI KEMITRAAN TEBU MILIK MASYARAKAT DENGAN PT GUNUNG MADU PLANTATION - Sari Dwika Ratri; Budiyono Budiyono; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2013)
This study aimed to describe sugar cane partnership owned by community with PT Gunung Madu Plantation in Kampung Gunung Agung , Terusan Nyunyai Subdistrict, Central Lampung regency. the pressure point in this study are land owned by cane farmers partnerships, income, partnership benefits, and the response of farmers to the partnership.This study uses descriptive method. the population in this study are 18 independent cane farmers, and all of them are respondents of the study (study population). The Data collected by observation, interviews, questionnaires, and documentation. Data are analyzed with percentage tabulation technique , and it is used as a basic interpretation and description in making this research report.The results of this study show that: (1) the total land area of 34.75 ha partnerships farmers, while the farmers' land area average of 1.9 ha (2) Total income of the entire partnership sugarcane farmers Rp. 574.700.000/year, on average each farmer income Rp. 31.928.000/year. (3) The benefits of partnering farmers obtain capital loan of Rp. 9.275.000/farmer and technical assistance to increase production, which is 148.6 tons / farmers with an average income of Rp. 31.928.000/year/farmer (4) the majority of respondents (88.89%) support the existence of independent cane partnership initiated by PT Gunung Madu Plantation because it can provide the increasing income for the farmer.Key words: Description, partnership, society